A New Method on Inshore Ship Detection in High-Resolution Satellite Images Using Shape and Context Information - Ge Liu; Yasen Zhang; Xinwei Zheng; Xian Sun; Kun Fu; Hongqi Wang (IEEE geoscience and remote sensing letters, 2014)
In this letter, we present a new method to detect inshore ships using shape and context information. We first propose a new energy function based on an active contour model to segment water and land and minimize it with an iterative global optimization method. The proposed energy performs well on the different intensity distributions between water and land and produces a result that can be well used in shape and context analyses. In the segmented image, ships are detected with successive shape analysis, including shape analysis in the localization of ship head and region growing in computing the width and length of ship. Finally, to locate ships accurately and remove the false alarms, we unify them with a binary linear programming problem by utilizing the context information. Experiments on QuickBird images show the robustness and precision of our method.